Meniti Kegamangan Mencapai Harmoni: Kajian Antropologi terhadap Hukum yang Berkenaan Tanah pada Masyarakat Osing-Banyuwangi - Dominikus, Rato (Jurnal Hukum Progresif, 2005)
The aimed of this study to understand the law relating to land in cosmology of Osing society and the cosmology of Osing society.